Religião como objeto de ciência: a ideia de uma disciplina epistemologicamente autônoma a partir de uma abordagem definicional - Figueiredo, Nestor (2022)
This thesis is a historical-comparative analysis of central metatheoretical questions for the Science of Religion, which since the 1870s, when it emerged as an academic enterprise in Europe, has been facing a fundamental problem, whose answer justifies its existence: what is religion, in the first place? Consequently, how can we study this object to derive knowledge from it and provide scientifically valid explanations? The objective is to reflect on the epistemological foundations of the discipline, considering a definitional approach as a methodological starting point that, we argue, guided both its scope and its agenda within a research program with scientific intent. Therefore, the definitional problem is the central metatheoretical question to be investigated, since from it we can derive equally fundamental questions. We argue that an answer to this problem is mandatory for science that takes religion as an exclusive object of study. Thus, as an area of knowledge, this discipline needs to say what religion is from a scientific point of view. Furthermore, the definition of this concept needs not only to exist, but above all to be assumed academically by the discipline, since it is from it, as we will demonstrate throughout the thesis, that the Science of Religion structures its epistemology. Finally, we consider that renouncing this “categorical imperative” can mean the continuity of an anarchic theoretical-methodological model, established anyway by definitions of other disciplines that approach “religion” from their own objects and theoretical frameworks. Methodologically, we started with an extensive bibliographic review on the central issue, followed by a more technical discussion regarding the term religion itself, after which we carried out a historical-comparative analysis of this epistemology in three decisive moments for the discipline: the classical period, the phenomenological and the cognitive-evolutionary, when we rescue the debate around the definitional question through its protagonists, notably the founders of the Science of Religion: Friedrich Max Müller, Cornelis Petrus Tiele, Pierre Daniel Chantepie de la Saussaye. The thesis concludes by arguing in favor of a scientifically established definitional approach, supported by an original hypertextual model of analysis, based on a consistent and significant sample of definitions of religion, representative of a good part of the theories around this issue, which points to a consensus minimum at this level, in addition to considering some important challenges that must be faced in a scenario of post-definitional epistemological autonomy.